2018
DOI: 10.15243/jdmlm.2018.052.1111
|View full text |Cite
|
Sign up to set email alerts
|

Trend analysis of temperature and rainfall in south gonder zone, anhara ethiopia

Abstract: Abstract:This study mainly focuses on exploring trend analysis of temperature and rainfall in the case of south Gonder zone. The analysis is based on the temperature and rainfall variation in south Gonder zone over three stations at Addis Zemen, Nefas Mewcha and Mekane Eyesus. The duration of the study period for temperature and rainfall data was chosen as 1996-2015 for Addis Zemen, 1986-2015 for Nefas Mewcha and 1996-2015 for Mekane Eyesus. The Belg rainfall have been found much more variable (>30%) than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 12 publications
3
13
0
Order By: Relevance
“…This implies that the pattern of mean maximum temperature was moved in the normal distribution mood with no sign of high extreme events than steadily increasing. Similar patterns of an increasing trend with mean annual maximum temperature observed in different parts of Ethiopia have been reported by other researchers (Hailu et al 2018;Miseker et al 2017;Tefera and Agena, 2016;Solomon et al 2015;Birhan, 2018).…”
Section: Trend Analysis Of Monthly Maximum Temperaturesupporting
confidence: 88%
“…This implies that the pattern of mean maximum temperature was moved in the normal distribution mood with no sign of high extreme events than steadily increasing. Similar patterns of an increasing trend with mean annual maximum temperature observed in different parts of Ethiopia have been reported by other researchers (Hailu et al 2018;Miseker et al 2017;Tefera and Agena, 2016;Solomon et al 2015;Birhan, 2018).…”
Section: Trend Analysis Of Monthly Maximum Temperaturesupporting
confidence: 88%
“…In line with the present study, some previous studies (Kenawy et al, 2012;Getachew, 2018) scrutinized precipitation trend in North Ethiopia, and reported non-significant decreasing trends of annual and seasonal precipitations. Note: ** and *statistically change of climatic variables at α = 0.01 and 0.05 respectively, ns = non-significant change, MAM = March, April and May, JJA = June, July and August…”
Section: Seasonal and Annual Precipitation Trendssupporting
confidence: 92%
“…The Mann-Kendall trend test for annual minimum temperature revealed statistically significant increasing trend for Chennek and Guhala stations Similar to Birhanu Getachew (2017). However, annual minimum temperature showed an increasing trend in all stations (Table 1).…”
Section: Observed and Perceived Climate Change And Variability Tempermentioning
confidence: 78%
“…However, a decreasing trend was seen in Debark and Guhala stations (Table 3). Similarly, Birhan Getachew (2017) found insignificant trend in annual rainfall. Figure 5 showed that Amba-Giorgis have a positive slope with increasing rainfall and Guhala has a negative slope that revealed decreasing rainfall.…”
Section: Rainfall Change and Variabilitymentioning
confidence: 90%